287 Impact of pre- and Post-Natal Nutritional Extremes on Responsiveness of Ovariectomized, Sexually Mature Heifers to a Neurokinin B Agonist During Progesterone Dominance. (21st September 2022) - Garza, Viviana; Kellerman, Julie I; Cardoso, Rodolfo C; Williams, Gary L
Abstract: Objectives were to test the hypothesis that nutritional extremes during prenatal development interact with postnatal nutrition during the juvenile period of heifers to impact KNDy neuron responsiveness to a neurokinin B (NKB) agonist (Senktide) during progesterone dominance. Heifers were selected from a larger population programmed nutritionally using a 3x2 factorial arrangement of pre- and post-natal diets. Bos indicus-influenced cows (n = 95) were fed to achieve body condition scores (BCS; 1-9 scale) of 3-3.5 (L; thin), 5.5-6 (M; moderate), or 7.5-8 (H; obese) by the onset of the third trimester and maintained thereafter. Heifer offspring were weaned at 3-3.5 mo of age and assigned to either a low- (L; 0.5 kg/day) or high-gain (H; 1 kg/day) diet until 8 mo of age, then fed a common diet until puberty. For the current experiment, heifers (n = 18; 6/group) representing LL, MH, and HH combinations were ovariectomized postpubertally (17.1 mo of age) and received estradiol (E2) replacement to maintain basal E2 concentrations at 2-4 pg/mL. To achieve progesterone dominance, 3 CIDR devices were placed intravaginally 6 days prior to the initiation of Senktide challenge. Heifers were sampled for a 4.5-h period and received intravenous injections of saline or Senktide (14.8 ug/kg I.V.) at 0, 90, and 180 min. Jugular blood samples were collected at 10-min intervals for radioimmunoassay of LH. Irrespective of Senktide treatment, heifers in the MH group had greater pulse amplitudes (P = 0.016) and mean concentrations (P < 0.0001) of LH compared with both the HH and LL groups. Senktide treatment increased (P = 0.003) concentrations of LH compared with saline in all groups; however, the response to Senktide was greatest in the MH group compared with HH and LL. Pre- and postnatal nutritional extremes appear to interact to impact KNDy neuron responsiveness to NKB receptor signaling in heifers.